2012
DOI: 10.13073/0015-7473-62.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Wood Properties of Young Acacia mangium Trees Planted in Indonesia

Abstract: This study evaluated the wood properties of 5- and 7-year-old Acacia mangium trees planted in West Java, Indonesia. A plot (20 by 20 m) was selected in each stand. The stem diameter and stress-wave velocity (SWV) were measured for all trees (n = 24 and 18 for 5- and 7-y-old trees, respectively) in the plots. Core samples were taken from all trees in each plot using an increment borer to measure the basic density (BD) and compressive strength parallel to the grain (CS). The mean ± standard deviation stem diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 11 publications
6
27
0
3
Order By: Relevance
“…4). The results obtained in the present study were similar to those obtained in research on other tropical hardwood species (Ishiguri et al 2012b, Makino et al 2012, Istikowati et al 2014. Furthermore, as shown in Table 2, no significant differences in basic density were found among growth categories.…”
Section: Effects Of Radial Growth Rate On Anatomical Characteristics supporting
confidence: 90%
See 4 more Smart Citations
“…4). The results obtained in the present study were similar to those obtained in research on other tropical hardwood species (Ishiguri et al 2012b, Makino et al 2012, Istikowati et al 2014. Furthermore, as shown in Table 2, no significant differences in basic density were found among growth categories.…”
Section: Effects Of Radial Growth Rate On Anatomical Characteristics supporting
confidence: 90%
“…It has been reported that xylem maturation depends on the diameter growth in tropical fast-growing tree species, such as A. mangium, F. moluccana, and others (Honjo et al 2005, Kojima et al 2009a, Makino et al 2012, Nugroho et al 2012. On the other hand, xylem maturation depends on cambial age in some tropical species that are not considered to be fast-growing species, such as Shorea acuminatissima and Tectona grandis (Ishiguri et al 2012b.…”
Section: Xylem Maturation In D Mollissimummentioning
confidence: 99%
See 3 more Smart Citations